Deflexões ao redor de buracos acústicos canônicos - RODRIGUES, Luiz Felipe Garça (2023)
Black holes are an extraordinary consequence of the theory of general relativity, ﬁrst predicted by Schwarzschild’s solution, the ﬁrst of Einstein’s equations. These objects are able to considerably deviate the light path and even trap it due to their strong gravitational interaction. However, they are objects that are far out of reach for detailed study, so that acoustic analog models of gravitation have been proposed by the physicist William George Unruh in order to analyze some properties of black holes in ﬂuid-dynamic systems. In this monograph, the study of the canonical acoustic hole - acoustic analogue to Schwarzschild’s black hole - is presented, focusing in the deﬂection of sound waves caused by it in order to compare with the light deﬂection caused by a Schwarzschild black hole. From the geodetic equations, the trajectory behavior of photons traveling far from a black hole is analyzed and the same process is applied to the study of sound waves passing far from a canonical acoustic hole. Deﬂection angles in both cases are found to depend on the impact parameter, in addition to the event horizon radius (of the black or acoustic hole). However, the deviation in the sound wave path by the acoustic hole is smaller than the deviation of light by the black hole. It is concluded that this diﬀerence in the deviations stems from the fact that the geometries are diﬀerent from each other, despite having a similar structure. This is a consequence of the fact that both systems are fundamentally distinct.